Artificial Intelligence Empowerment for Industrial Innovation and Value Chain Upgrading: Mechanisms and Pathways (Journal of economic and management development research, 2026)
Against the backdrop of the rapid development of the digital economy, artificial intelligence (AI) has increasingly penetrated the research and development, production, circulation, and service stages of industrial value chains, becoming a key driver for industrial innovation and value chain upgrading. AI enhances information processing, optimizes resource allocation, and reshapes business models, thereby improving industrial collaboration, innovation capacity, and value creation. While policy initiatives and market demand jointly promote digital transformation and value chain restructuring, the uneven maturity of AI technologies, disparities in enterprise digital capabilities, and insufficient data collaboration across value chains still constrain AI-enabled benefits. This study analyzes the mechanisms through which AI empowers industrial innovation and value chain upgrading from the perspectives of technological element restructuring, organizational capability enhancement, and value chain structural evolution, and further proposes pathways concerning data governance, intelligent technological integration, and innovation ecosystem collaboration. The findings suggest that differentiated strategies should be formulated according to industry characteristics and enterprise development stages, in order to promote deep digitalization and value chain modernization in the real economy.
Keywords: Artificial intelligence; Industrial innovation; Value chain upgrading; Digital economy; Organizational capability